Effects of grazing systems on pasture production and quality of Brachiaria brizantha and liveweight gain of lambs . - Ginting, Simon P; Pond, K.R (Indonesian Journal of Animal and Veterinary Sciences, 1996)
Grazing cycle beyond parasite survival time can reduce the level of parasite contamination, but at the same time it may depress the quality of available forage for animal production . A study was conducted to evaluate the effects of grazing management systems on the production and quality of Brachiaria brizantha and the performance of lamb grazing this pasture . A total of 72 male lambs aged from 3 to 4 months were used . The lambs were divided into 3 groups and randomly allocated to receive one of the following grazing treatments : GMl-pastures were grazed for 6 weeks and then rested for 6 weeks, GM2-pastures were grazed for 1 week and then rested for 6 weeks, and GM3-pastures were grazed for 12 weeks and then rested for 12 weeks . The herbage mass measured before and after grazing was greatest (P<0.01) forGM3. Canopy compositions before grazing as not different (P>0 .10) among the three grazing methods, while after grazing, the proportion of stem fraction was highest and leaf fraction was lowest for GM3 (P<0 .01) . The in vitro dry matter digestibility (IVDMD) of plucked samples were not different (P>0 .10) among the grazing methods. The crude protein (CP) concentration was lower (P<0 .05) for GM3 as compared for GM 1 and GM2, and a difference of two percentage unitmay be of biological important. The changes in IVDMD and CP concentration of the plucked samples collected throughout grazing cycle remained reasonably steadily . Average daily gains (ADG) were low and not different (P>0 .10) across grazing treatment and ranged from 29 to 35 g. It was concluded that a 12-week grazing cycle while could increase the herbage mass of Brachiaria brizantha did not decrease feed intake, the digestibility and the crude protein concentration of the consumed forage . Therefore, this gazing system could be considered as a means to control parasite establishment on pastures. Key words : Grazing systems, herbage mass, forage quality, sheep